Não incidência de ITBI: uma proposta para o município de Fortaleza - Lima, José Arnoldo Fiúza (2022)
The study had its core in the analysis of the non-levy of the Property Transfer Tax in the city of Fortaleza. As it is a topic with suggestive legislation to generate difficulty in understanding and operationalization, the presentation of proposals for instruments was envisaged aimed at contributing to the improvement of procedural efficiency. In this sense, the main purpose was to present a proposal for products to guide taxpayers and tax authorities in the processing of this type of tax exoneration. Given the above, a single case study strategy was adopted, with the Fortaleza Finance Department (SEFIN) as the unit of analysis, framing the research as qualitative in nature, being descriptive in terms of purposes, and documentary and field procedures. The study was supported by primary and secondary data. The collection of primary data was carried out through a questionnaire. Secondary data resulted from the survey of operational routines, as well as the tax processes of the non-levy of Property Transfer Tax dispatched, in the period from 2016 to 2020, at SEFIN. For the analysis, the framework of Scholes and Wolfson (1992) was adopted, developed specifically for tax studies. In the research, it was concluded that the adoption of procedures due by the Organ has already contributed to leverage the entry of resources into the public treasure, however, with the products developed: procedural flow model and didactic and instructional material, improvements aimed at providing the Municipal Tax Authorities with a greater increase in collection, and, for taxpayers, an efficient tax planning that is adequate to the inherent legislation.